In-situ microcantilever deflection to evaluate the interfacial fracture properties of binary Al2O3/SmAlO3 eutectic. Issue 10 (August 2019) - Ma, Yong-Hui; Wang, Zhi-Gang; Ouyang, Jia-Hu; Dillon, Shen J.; Feng, Lin; Wang, Yu-Jin
Abstract: This study aims to elucidate the impact of interfacial microstructure and properties on fracture toughness in binary Al2 O3 /SmAlO3 eutectic and its polycrystalline samples via in-situ microcantilever deflection tests. Al2 O3 -SmAlO3 eutectic with semi-coherent heterointerfaces exhibits superior interfacial toughness of 2.85 MPa⋅m 1/2 relative to randomly oriented interfaces in Al2 O3 /SmAlO3 polycrystals. SmAlO3 grain boundaries (GBs) have the lowest toughness of 1.97 MPa⋅m 1/2 among all the constituents, i.e. bulk and interfaces. The toughness of eutectic Al2 O3 -SmAlO3 interfaces is intermediate between polycrystalline Al2 O3 -Al2 O3 GBs and SmAlO3 -SmAlO3 GBs. Fracture toughness values of both polycrystalline and eutectic Al2 O3 -SmAlO3 samples obtained by mesoscopic indentation measurements are in the range of 4.2 MPa⋅m 1/2 to 4.7 MP⋅m 1/2, which exceeds all constituent components. Much of the overall fracture toughness of the bulk samples derives from microstructural and geometric energy dissipation mechanisms.